Getaran Torsional Sistem Propulsi Kapal Tug Boat - alamsyah, Alamsyah; Hapsari, Dessy Purwita; Wulandari, Amalia Ika; Setiawan, Wira; Pawara, Muhammad Uswah (Jurnal Penelitian Enjiniring, 2021)
The Torsional Vibration of Propulsion System of the Tug Boat Ship. Vibrations that occur in the ship's propulsion system can cause reduced operating capability and cause damage to the ship's components, one of the vibrations that occur in the ship's propulsion system is torsional vibration. The purpose of this study was to determine the value of torque oscillations in Tugboat Ship propulsion systems and to find out the value of noise radiation following ICES 209 standard with variations of ST 60 steel material, stainless steel, and carbon steel, using analitical methods. The results obtained by the torque oscillation value of the propulsion system from Tugboat Ship BPW 3 with the variation of ST 60 steel material is 0.0004854, while for carbon steel material, the torque oscillation value is 0.0004690 and the propulsion system that uses stainless steel material variation is 0.0004527. The level of noise radiation (SL) that occurs in propulsion systems using variations of ST 60 steel material is 133.22 dB, while for carbon steel material is 133.23 dB and for stainless steel material is 133.25 dB, of the three noise radiation values (SL ) produced, is still included in the ICES 209 noise level standard.